PUBLIC BILLS AND RESOLUTIONS - MOAKLEY (Tufts Archival Research Center, 2007)
Handwritten; The Congressional Record for the House of Representatives for March 3, 1980 including bill H.R. 6675, requiring cigarette manufacturers to meet minimum standards as to the capacity for igniting smoldering fires in upholstery and mattresses. Proposes a five minute cap when at that time the cigarette would then self extinguish. Emphasizes this is not an antismoking bill, but a pro-safety bill.